2011
DOI: 10.5937/ratpov1102313s
|View full text |Cite
|
Sign up to set email alerts
|

On the role of genes determinate, late flowering and fasciata in the morphogenesis of pea inflorescence

Abstract: The effects of mutations determinate (det), late flowering (lf), fasciata (fa, fas), and nodulation4 (nod4) on development of inflorescence in pea were characterized. All listed mutations distort functions of stem apical meristem and influence development of axillary flower-bearing axis (short paracladium) leading to formation of terminal flower and bracts. Structure of flower terminating short paracladium was analyzed and hypothesis on origin of its structure was proposed. Scheme of genetic network in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In most taxa, it is either structurally discernible (flag in Papilionoideae or vexilloid petal in Caesalpinioideae) or it is the only petal with the other four petals reduced (Swartzia, Amorpha and many others). This petal together with the opposed stamen and the adaxial sepals is the most stable elements of pea flower in different floral mutants (Sinjushin 2011(Sinjushin , 2014. Considering that a correlation between adaxial petal and free stamen is constant for some derived legume taxa, the absence of staminal fusion in radialized teratic flowers is easy to explain.…”
Section: Discussionmentioning
confidence: 97%
“…In most taxa, it is either structurally discernible (flag in Papilionoideae or vexilloid petal in Caesalpinioideae) or it is the only petal with the other four petals reduced (Swartzia, Amorpha and many others). This petal together with the opposed stamen and the adaxial sepals is the most stable elements of pea flower in different floral mutants (Sinjushin 2011(Sinjushin , 2014. Considering that a correlation between adaxial petal and free stamen is constant for some derived legume taxa, the absence of staminal fusion in radialized teratic flowers is easy to explain.…”
Section: Discussionmentioning
confidence: 97%
“…Flowers of fasciated pea (and other legumes, reviewed in (Sinyushin 2010)) mutants remain normal, while in fasciated plants of Arabidopsis both stem and floral meristems become affected. The axillary raceme becomes terminated with anomalous flower in some fasciated plants (Sinjushin 2011). More, certain similarity is observed in a genetic regulation of SAM activity and symbiotic nitrogen fixation (nodulation), the latter phenomenon being a specific feature of Fabaceae.…”
Section: Stem and Inflorescence Architecturementioning
confidence: 97%
“…Galega). Such ontogenic switch is unusual for pea and other members of Fabeae tribe, so the phenotype of such determinate forms was studied precisely (Singer et al 1990, Sinjushin 2011. It was demonstrated that det plants also produce terminal flowers on axillary racemes the latter sometimes becoming bracteous.…”
Section: Stem and Inflorescence Architecturementioning
confidence: 99%
“…2 ). Results of subsequent complementation tests (locus identity test crosses) that explain the genetic basis of fasciata phenotype in pea lines from the Blixt’s, Gottschalk’s, Marx’s, Święcicki’s and Sinjushin’s collections were as follows (Święcicki 2001 ; Sinjushin et al 2006 ): no typeline registered by Blixt ( 1977 ) exists in the main Pisum collections for the fas gene from LGIII; Sinjushin et al ( 2006 ) and Sinjushin ( 2011 ) suggested that the two lines, JI2771 and mutant Shtambovii , have the fas gene, fasciation in most of the tested lines is controlled by the fa gene from LGIV, dichotomous branching appeared to be controlled by the allele in the fa locus (symbol fa bif was suggested), an exception is the fasciation in the accession Wt 12185 as controlled by a gene different from the fa locus; for fa in LGIV, the symbol fa1 (and fa1 bif ) was suggested and fa2 for the new gene in the type line Wt 12185.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…no typeline registered by Blixt ( 1977 ) exists in the main Pisum collections for the fas gene from LGIII; Sinjushin et al ( 2006 ) and Sinjushin ( 2011 ) suggested that the two lines, JI2771 and mutant Shtambovii , have the fas gene,…”
Section: Introductionmentioning
confidence: 99%